Каштанка: рассказы : [для среднего школьного возраста] / А. П. Чехов ; художник Е. Володькина - Чехов Антон Павлович (Внеклассное чтение, 2018)
Экземпляры: (20190429) / Инвентарный номер: 40999 / Цена: 82.60 / Сис.шифр: Р1 / Авт.знак: Ч-56 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1